Every breath you take [compact disc, unabridged] - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion novel., 2017)
"Queen of Suspense" Mary Higgins Clark and Alafair Burke are back with their fourth book in the New York Times bestselling Under Suspicion series; Every Breath You Take follows television producer's Laurie Moran investigation of the unsolved Met Gala murder-in which a wealthy widow was pushed to her death from the famous museum's rooftop.